The Effect Of Psychological Counseling On The Development Of Psychological Skills and the Level Of First Class Soccer Referees (Baghdad governorate) - Qasem, Sabah; Sabah, Nahla (Journal of Physical Education, 2018)
The Effect Of Psychological Counseling On The Development Of Psychological Skills and the Level Of First Class Soccer Referees (Baghdad governorate)Referees need psychological skills through psychological counseling sessions that aimed at developing the referees' performance levels. The researchers used the experimental method. The subjects were (10) referee for the experiment and (4) for pilot study. The experimental group took counseling sessions for eight weeks with one session per week while the controlling group continued their traditional program. The researchers concluded that psychological counseling plays a great role in developing referees' psychological skills. Finally they recommended that all referees should be included in psychological counseling session to develop their performance during matches.Keywords: referees, psychological counseling, psychological skills.